الحق في المساعدات الإنسانية وإمكانية استخدام القوة في إطار الفصل السابع من ميثاق الأمم المتحدة لتأمين تلك المساعدات: دراسة نقدية تحليلية، - أبو صيني، سامح محمد ابراهيم (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2011)
The right to humanitarian assistance, in cases of natural and man-made disasters, is considered among the most important rights safeguarded by the rules of international public law. The rules of international humanitarian law guarantee the regulation and implementation of this right during conflicts and extreme disasters. The rules of international law for human rights, as well as international, regional and bilateral treaties on this issue, are considered the legal basis for this right in cases of natural disasters, earthquakes, volcanoes, drought and floods. Hence, aid and protection should be made permanently available. Providing humanitarian aid or assistance means enabling individuals to enjoy their rights and retrieve their individual independence which presents the only guarantee for their survival. Humanitarian assistance, in the context of international law, is viewed as a temporary stage, wherein acknowledgment of the status quo as well as the legal rights of endangered individuals must be made. In practice, such acknowledgment must be related to relief work. A sovereign state is responsible for the safety of its citizens and their rescue during disasters such as famine and genocide. Nevertheless, if such a state is incapable of carrying out these duties or refrains from carrying them out, the international society would be responsible for the same. The rules of international law recognize only one right for the interference with the internal affairs of states. This right is provided for in the Seventh Chapter of the United Nation's Charter. The role of checking the applicability of this right is assigned to the Security Council of the United Nations which interprets the acts of a certain state as either being a threat to international peace and security or otherwise. On several occasions, the Security Council considered humanitarian interests while carrying out military campaigns or peace keeping operations. Yet, peace keeping operations adhere to general requisites which are related to maintaining international peace and security, while humanitarian interests remain a secondary issue. Moreover, the Security Council did not explicitly or clearly acknowledge that the breaches of humanitarian law or the oppression or persecution of civilians, for which the Council decided to interfere in order to resolve, creates a threat to international peace and security. Nevertheless, the main guarantee for the successful implementation of humanitarian assistance is that the humanitarian work remains within the framework of protection and relief, and far from any attempts to support or sustain military operations for the purpose of attracting attention and politicizing such acts. Humanitarian assistance has the features of being exceptional and temporary, and is supplementary to national and local authorities, and hence is not a substitute to the role of the state.